Plasma protein antimicrobial substitution at negligible risk - Gatnau R.; Polo J.; Robert E. (Feed manufacturing in the Mediterranean region. Improving safety: From feed to food, 2001)
The use of blood derived products has increased worldwide because of their wide functional characteristics. Food, feed, animal and human health are the main industries using those products. The main products used by the feed industry are plasma protein and red cell fraction. Those are especially important in swine and pet food. The production system is described. A risk assessment has been done that indicates that the risk of blood products usage is negligible. Plasma is a biosafe product as far as bacteriology, virology and BSE are concerned. The production benefits of plasma are well documented: increased feed intake, growth performance, decreased diarrhoea incidence, protected intestinal function and morphology. The most plausible modes of action for those effects are palatability, digestibility and intestinal protection. The fraction responsible for those effects is the high molecular fraction.
3. Conference of Feed Manufacturers of the Mediterranean, 2000/03/22-24, Reus (Spain)